2013
DOI: 10.1177/0883073812473644
|View full text |Cite
|
Sign up to set email alerts
|

Views of Recently First-Certified US Child Neurologists on Their Residency Training

Abstract: We surveyed child neurologists first certified in "Neurology with Special Qualification in Child Neurology" by the American Board of Psychiatry and Neurology (ABPN) between 2001 and 2010 using a 24-item questionnaire. Respondents (n = 204, 54% response rate) were between the ages of 30 and 59 years (54% male), and 68% completed adult neurology training in a 10- to 12-month, primarily inpatient block. Sixty-two percent of the sample completed subspecialty fellowship training and 82% currently reported practicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…Before 2014, a survey of neurologists completing first certification between 2001 and 2010 showed that 68% of respondents reported their training programs involved 10-12 months of adult neurology in the PGY-3. 6 While the responders to the aforementioned survey were a different population than those of the PD surveys, these data still support the notion that, over This study also found that programs with children's hospital GME funding (for either 2 or 3 years) tended to be larger than those using predominantly adult institution GME funding. One possible explanation for the association is that children's hospitals with their own GME funding are more likely to be large regional referral centers with greater patient volume and more need for residents.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Before 2014, a survey of neurologists completing first certification between 2001 and 2010 showed that 68% of respondents reported their training programs involved 10-12 months of adult neurology in the PGY-3. 6 While the responders to the aforementioned survey were a different population than those of the PD surveys, these data still support the notion that, over This study also found that programs with children's hospital GME funding (for either 2 or 3 years) tended to be larger than those using predominantly adult institution GME funding. One possible explanation for the association is that children's hospitals with their own GME funding are more likely to be large regional referral centers with greater patient volume and more need for residents.…”
Section: Discussionsupporting
confidence: 52%
“…4 Reflecting these changes, the 2015 American Academy of Pediatrics and Child Neurology Society (CNS) Workforce Survey demonstrated that CN residents and practicing physicians favor an increased training emphasis on child-centric disciplines such as genetics and developmental disorders and a decrease in the amount of adult neurology training. 5 Other surveys have reinforced these changing ideas about the content of CN training 6,7 ; however, these viewpoints remain controversial. [8][9][10][11] The Program Requirements for Graduate Medical Education in Child Neurology, set by the Accreditation Council for Graduate Medical Education (ACGME) to achieve eligibility for board certification by the American Board of Psychiatry and Neurology, have also evolved.…”
Section: Discussionmentioning
confidence: 99%
“…The responses may not be representative of all training programs, although response rates were similar to other survey-based studies. 9,10 Selection bias may have skewed the results toward a greater importance/emphasis on cerebral palsy training as program directors more interested in cerebral palsy may have been more likely to respond. Furthermore, it is not clear how accurate program directors’ perceptions are with regard to the adequacy of training.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier survey, more than 80% of recently graduated child neurology residents reported that a training program with fewer or no adult neurology months would have better prepared them to diagnose and manage cerebral palsy. 10 Furthermore, children with cerebral palsy become adults with cerebral palsy, who continue to have very specialized needs, although it can be quite difficult to find adult neurology providers with cerebral palsy expertise. 11 These gaps could be addressed in training, as adult neurology trainees rotate through pediatric neurology experiences.…”
Section: Discussionmentioning
confidence: 99%
“…16 One advantage of this proposed change is that it would give child neurology residents more time to explore subspecialties such as genetics and developmental neurology earlier in residency. 17…”
Section: Other Methods To Support Residents In the Fellowship Applica...mentioning
confidence: 99%